DYNAMICS OF MORBIDITY AND MORTALITY FROM MALIGNANT BONE NEOPLASMS IN UZBEKISTAN - K. G. Abdikarimov; M. A. Gafur-Akhunov (Journal Park Publishing, 2025)
An epidemiological analysis of the dynamics of morbidity and mortality from malignant bone neoplasms in the Republic of Uzbekistan was carried out in this study. Based on data from the State Oncological Register, it was established that more than 25,000 new cases of malignant tumors are registered annually in the country, of which about 320 cases (1.3%) are tumors of bone tissue. Over the past nine years, a steady downward trend has been observed in both the absolute number of cases and in morbidity and mortality rates per 100,000 population among both men and women. The largest proportion of patients with malignant bone neoplasms belongs to the 20–44-year-old age group. About 3,000 patients with this diagnosis are currently under dispensary observation in Uzbekistan. The results obtained indicate a decrease in the prevalence and lethality of malignant bone neoplasms during the study period. At the same time, significant age-related differences in the structure of oncological morbidity were revealed, which requires further in-depth study of risk factors and improvement of preventive measures.
Keywords: Malignant bone neoplasms, morbidity, mortality, epidemiology.